The Indian mutual fund industry : a comparative analysis of public vs private sector performance - Sekhar, G. V. Satya; SpringerLink (Online service) (London : Palgrave Macmillan UK, 2014)
Dr. Sekhar offers comprehensive knowledge on the mutual fund industry in India and provides ready-made practical information for investors. He presents an overview of investment patterns for both public and private sector mutual funds, and analyses the performance of selected schemes using various measures of risk.
Keywords: Finance; Banks and banking; Investment banking; Securities